Food safety risk assessment for traditional value chains under a One Health perspective - Sinh Dang Xuan; Sirikachorn Tangkawattana; Makita, K.; Chi Nguyen; Tuan Nguyen; Unger, Fred (International Livestock Research Institute, 2025)
The training on “Food safety risk assessment for traditional value chains under a One Health perspective” was conducted on 23–24 September 2025 at the Faculty of Veterinary Medicine, Khon Kaen University (KKU), Thailand. Organized by the International Livestock Research Institute (ILRI) in collaboration with KKU and Rakuno Gakuen University (RGU), the workshop brought together approximately 40 participants from diverse professional backgrounds, including food safety authorities, researchers, veterinarians, and academic staff from Malaysia, Japan, China, Lao PDR, the Philippines, Vietnam, Indonesia, and Thailand. Over two days, the training provided a comprehensive combination of theoretical and practical knowledge on food safety hazards, risk assessment methodologies, and the integration of One Health principles. Sessions included overviews of food safety situations in low- and middle-income countries, principles of risk analysis, Codex-based risk assessment approaches, and case studies such as Salmonella in pork and the LAWA model for liver fluke control. Participants engaged in interactive group exercises to practice risk assessment, develop value chain models, and interpret results within a One Health framework. At the end of the training, participants had acquired practical skills to conduct food safety risk assessments, analyze and interpret results, and apply One Health solutions within their national contexts. The workshop also promoted regional collaboration and knowledge exchange, identifying future priorities for capacity building, network development, and the integration of One Health concepts into national food safety systems and curricula. This event reinforced the importance of multidisciplinary approaches and cross-country learning in strengthening food safety in traditional value chains across the region.